Dextrose intravenous fluid therapy in labor reduces the length of the first stage of labor. (September 2018) - Riegel, Melissa; Quist-Nelson, Johanna; Saccone, Gabriele; Locci, Mariavittoria; Shrivastava, Vineet K.; Salim, Raed; Fisher, Allan; Nordstrom, Lennart; Kunselman, Allen R.; Repke, John; Fong, Alex; Smulian, John; et al.
Abstract: The aim of this systematic review with meta-analysis was to evaluate the effect on length of labor when patients receive IVF with or without dextrose. Searches were performed in electronic databases from inception of each database to May 2018. Trials comparing intrapartum IVF containing dextrose (i.e. intervention group) with no dextrose or placebo (i.e. control group) were included. Only trials examining low-risk pregnancies in labor at ≥36 weeks were included. Studies were included regardless of oral intake restriction. The primary outcome was the length of total labor from randomization to delivery. The meta-analysis was performed using the random effects model. Sixteen trials (n = 2503 participants) were included in the meta-analysis. Women randomized in the IVF dextrose group did not have a statistically significant different length of total labor from randomization to delivery compared to IVF without dextrose (MD −38.33 min, 95% CI −88.23 to 11.57). IVF with dextrose decreased the length of the first stage (MD −75.81 min, 95% CI −120.67 to −30.95), but there was no change in the second stage. In summary, use of IVF with dextrose during labor in low-risk women at term does not affect total length of labor, but it does shorten the first stage of labor.